Peculiarities of neutron irradiation influence on GaP light-emitting structures - Litovchenko, P.; Litovchenko, A.; Konoreva, O.; Opilat, V.; Pinkovska, M.; Tartachnyk, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
GaP LEDs irradiated by reactor neutrons were studied by optical and electrical methods. The observed emission intensity degradation is related with two factors: 1) radiation fields that destroy bond excitons and 2) decrease in the free charge carrier concentration, which is caused by their capture by radiation defects. Study of currentvoltage characteristics at 77 K by highly precession methods has revealed the appearance of N-shaped negative differential region caused by carrier tunneling onto deep levels in quantum wells, which might exist in initial and irradiated p-n structures. In some cases, improvement of current-voltage characteristics after neutron irradiation is observed. An assumption is made about the radiation-stimulated origin of this effect.